Respostas funcionais de diferentes tamanhos de Tilápia do Nilo; Oreochromis niloticus; predando zooplâncton - Santos, Pablo Lucio Rubim Costa dos (2010)
The Nile tilapia, Oreochromis niloticus, is an important omnivorous fish in the reservoirs of the semi-arid region of Brazil. Throughout its growth tilapia s feeding behavior changes from a visual predator of zooplankton to a filter-feeder, collecting suspended particulate matter, including planktonic organisms, through pumping. This feature results in different impacts of tilapia on plankton community as the fish grows. Aiming to quantify the functional response of different sizes of Nile tilapia on zooplankton experiments in microcosms scale in the laboratory and in mesocosm scale in the field were carried out. The data were fitted to four different models of functional response. The best fits were obtained for nonlinear models in laboratory experiments. While the experiments in mesocosms were the best settings for responses of type I (juvenile and adult tilapia) and type III (fry). The Manly's alpha index was used to evaluate the feeding selectivity of tilapia on the three main groups of the zooplankton in the experiments in mesocosms. The results show that: (i) rotifers were the preferred prey of fingerlings,(ii) copepods were rejected by fry and juvenile tilapia and (iii) adult fish fed non-selectively on copepods, cladocerans and rotifers. The functional response models obtained in this research can be applied to population models and help in modeling the dynamics of interactions between Nile tilapia and the planktonic communities in the reservoirs of the semi-arid